Hydrocarbon Nation : How Energy Security Made Our Nation Great and Climate Security Will Save Us - Hogan, Thor (Book collections on Project MUSE., 2018)
"In Hydrocarbon Nation, Thor Hogan looks at how four technological revolutions--industrial, agricultural, transportation, and electrification--drew upon the enormous hydrocarbon wealth of the United States, transforming the young country into a nation with unparalleled economic and military potential. Each of these advances engendered new government policies aimed at strengthening national and economic security. The result was unprecedented energy security and the creation of a nation nearly impervious to outside threats. However, when this position weakened in the decades after the peaking of domestic conventional oil supplies in 1970, the American political and economic systems were severely debilitated. At the same time, climate change was becoming a major concern. Fossil fuels created the modern world, yet burning them created a climate crisis. Hogan argues that everyday Americans and policymakers alike must embrace the complexity of this contradiction in order to help society chart a path forward. Doing so, Hogan explains, will allow us to launch a critically important sustainability revolution capable of providing energy and climate security in the future. Hydrocarbon Nation provides reasons to believe that we can succeed in expanding on the benefits of the Hydrocarbon Age in order to build a sustainable future."--EBSCO